Economic results of Croatian farms - Očić, Vesna; Bobić, Branka Šakić; Njavro, Mario (Applied Studies in Agribusiness and Commerce, 2016)
The objective of the paper is to provide an overview of the situation and performance of Croatian farms. Croatian farmers rarely keep business books and therefore farm level business data are deficient. Croatian accession to the European Union in 2013 brought numerous innovations to agricultural sector. One is introduction of Farm Accountancy Data Network (FADN) which aims to determine the impact of the Common Agricultural Policy on national agriculture of EU member states. The sample of Croatian FADN comprises 1,250 commercial farms. The paper brings results of agricultural sector financial analysis for the period 2011-2013. Total farm output decreased, but since the stronger decrease trend occurred in total inputs, this led to positive trend of gross and net farm income in the year 2013. Positive results are also shown at efficiency and productivity of Croatian farms. In the years 2011 and 2012 farms operated below the efficiency level while in 2013 efficiency increased above the efficiency level. In the observed period there was a 70% increase in productivity. The analysis shows that the most efficient farms are those in vegetables and flowers type. It also has the highest debt ratio due to their capital intensiveness. The vegetable and floriculture farms have the largest gross farm income in all three analysed years, but with a large drop in 2013, while the farms in type pigs and poultry have largest increase of gross farm income in last observed year.